(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
This article focuses on the process of adoption of the Constitution of the Republic of Uzbekistan and its essence, as well as the mechanisms of guaranteeing human rights by the constitution. At the same time, the main factors in the implementation of constitutional reforms of the Republic of Uzbekistan, which has set ambitious goals, are shown.